PWE-034 The clinical and economic cost of delirium following surgical resection for oesophageal malignancy. (28th May 2012) - Markar, S R; Smith, I; Low, D
Abstract : Introduction: Delirium is an under-estimated and serious complication following major surgery, particularly in the elderly population. The aim of this study was to identify pre-operative risk factors for delirium following oesophagectomy for malignancy, and investigate its impact upon short and long-term outcome. Methods: All patients undergoing oesophagectomy for cancer between 1991 and 2011 had information prospectively entered in an IRB-approved database. Patients were divided into two groups based upon the presence or absence of clinically-significant post-operative delirium, and were compared with respect to use of neoadjuvant therapy, medical co-morbidities, operative outcomes, post-operative complications, overall cost and survival. For the purposes of this study delirium was defined as an acute fluctuating confusional state that required intervention. Results: 500 patients were included in this analysis; 46 (9.2%) patients with post-operative delirium and 454 patients without. In the delirium group, age was significantly increased (71±8.1 yrs vs 63±10.9 yrs) and BMI was reduced (25±4.2 vs 27±4.8 kg/m 2 ). There were no significant differences in cardiac, pulmonary or renal co-morbidities, however ASA grade (2.8±0.4 vs 2.6±0.5) and Charlson Co-morbidity index (2.5±0.7 vs 2.3±0.6) were significantly increased in the delirium group. There were no significant differences between the groups in the use of neoadjuvant therapy. Analysis demonstrated that delirium was associated with a significantly longer hospital (14±7.5 vs 10.9±5.7 days) and ICU stay (3.6±3.8 vs 2.7±16.9 days). Furthermore post-operative delirium was associated with a significantly increased incidence of post-operative pneumonia (21.7% vs 7.9%), pneumothorax (10.9% vs 2.6%), re-intubation (10.9% vs 1.8%) and increased overall treatment costs ($28 223±13 018 vs $22 702±9689; p<0.05). Age was the only pre-operative predictor of post-operative delirium in multivariate modelling (OR 1.08; 95% CI 1.04 to 1.12, p<0.05). Patients were followed-up for an average of approximately 4 years. There was no significant difference between the groups in overall survival (1105±910 days vs 1273±1428; p=0.28). Conclusion: This study demonstrates that delirium is a risk factor for complicated post-operative recovery and increased treatment costs following oesophagectomy, and furthermore that age is independently predictive of its development. Focused screening will allow targeted preventative strategies to be employed in the peri-operative period to reduce complications and cost associated with delirium. Competing interests: None declared.